SynProt: A Database for Proteins of Detergent-Resistant Synaptic Protein Preparations - Pielot, Rainer; Smalla, Karl-Heinz; Mueller, Anke; Landgraf, Peter; Lehmann, Anne-Christin; Eisenschmidt, Elke; Haus, Utz-Uwe; Weismantel, Robert; Gundelfinger, Eckart D.; Dieterich, Daniela C. (Frontiers in Synaptic Neuroscience, 2012)
Chemical synapses are highly specialized cell-cell contacts for communication between neurons in the CNS characterized by complex and dynamic protein networks at both synaptic membranes. The cytomatrix at the active zone (CAZ) organizes the apparatus for the regulated release of transmitters from the presynapse. At the postsynaptic side, the postsynaptic density constitutes the machinery for detection, integration and transduction of the transmitter signal. Both pre- and postsynaptic protein networks represent the molecular substrates for synaptic plasticity. Their function can be altered both by regulating their composition and by post-translational modification of their components. For a comprehensive understanding of synaptic networks the entire ensemble of synaptic proteins has to be considered. To support this, we established a comprehensive database for synaptic junction proteins (SynProt database) primarily based on proteomics data obtained from biochemical preparations of detergent-resistant synaptic junctions. The database currently contains 2,788 non-redundant entries of rat, mouse and some human proteins, which mainly have been manually extracted from twelve proteomic studies and annotated for synaptic subcellular localization. Each dataset is completed with manually added information including protein classifiers as well as automatically retrieved and updated information from public databases (UniProt and PubMed). We intend that the database will be used to support modeling of synaptic protein networks and rational experimental design.